Gray platelet syndrome: Novel mutations of the NBEAL2 gene - Bottega, Roberta (2017)
Gray platelet syndrome (GPS) is a rare inherited macrothrombocytopenia characterized by reduction of a-granules in platelets and megakaryocytes associated with mild-tomoderate bleeding and myelofibrosis [1]. As reported in at least 28 unrelated families [1], GPS is caused by mutations of NBEAL2, the gene encoding for the neurobeachin-like-2 protein. NBEAL2 is a member of the family containing the BEACH (BEige And Chediak Higashi) domain, a conserved region involved in vesicular trafficking that may be critical for the a-granule development [2]. Here, we report novel mutations of NBEAL2 in two affected individuals (P1 and P2), who were previously diagnosed with immune thrombocytopenia (ITP) and then suspected to have GPS because of absence of azurophilic granules on May-Grunwald-Giemsa staining. In P1, sequencing analysis identified an € homozygous missense variant (c.6212G > C; p.Arg2071Pro; Supporting Information Fig. S1). Since her parents were not available for the segregation analysis, we hypothesised that the two mutant alleles were identical by descent because of homozygosity of all the polymorphic markers at the NBEAL2 locus (data not shown). Moreover, the potential hemizygous condition was excluded using statistical analyses of NBEAL2 amplicon coverage as previously reported (Supporting Information Fig. S1C) [3]. In P2, we detected one maternal nonsense (c.3839C > T; p.Arg1280*) and one paternal missense (c.6477C > G; p.His2159Gln; Supporting Information Fig. S1). The three NBEAL2 variants are reported in SNPs databases but with a minor allele frequency <0.01%.